PROFIL KLINIKOPATOLOGI LESI PRE KURSOR KARSINOMA KOLOREKTAL (KKR) DI RSUP SANGLAH DENPASAR PERIODE TAHUN 2018-2020 - I Wayan, Oka Semara Jaya; Saputra, Herman; Ekawati, Ni Putu; Juli Sumadi, I Wayan (E-Jurnal Medika Udayana, 2022)
ABSTRACT CRC precursor lesions are abnormal tissue growths in the colon and rectum that are not controlled but do not have the capacity to invade surrounding tissues. Good management if delayed in the long term causes the lesion to develop into colorectal carcinoma, a malignant condition that occurs in the colon and rectum. The purpose of this study was to determine the clinicopathological description of pre-cursor colorectal carcinoma lesions at Sanglah Hospital Denpasar in 2018- 2020. The study used secondary data by cross sectional (cross sectional) with a total sampling technique using data from the patient's medical record at the Anatomical Pathology Installation at Sanglah Hospital Denpasar. The number of data obtained during the study period as patients diagnosed as precursor TRC lesions were 55 samples which were then processed using SPSS ver 26 software. The results of the study obtained a profile of the clinicopathological characteristics of pre-cursor TRC lesions at Sanglah Hospital Denpasar in 2018- 2020 the most findings were adenoma low grade dysplasia as many as 26 cases (47.3%), occurring in the age group 60-69 as many as 15 cases (27.3%), experiencing clinical manifestations of blood during defecation with a total of 18 cases (26.9%), and most commonly found in the rectum as many as 29 cases (52.7%). This finding is useful because it can provide insight into the profile of the clinicopathological characteristics of pre-cursor TRC lesions at Sanglah Hospital Denpasar in 2018-2020. Further analytical research is needed to find the relationship between various variables. Keywords: profile, precursor lesion, colorectal carcinoma